Implementasi Algoritma Advance Encryption Standard dan Caesar Cipher pada Pesan Terenkripsi - Aditiya Hermawan; Anton Halim; Dera Susilawati; Intan Anjali Putri (Universitas Wahid Hasyim, 2023)
The development of information technology allows many people to communicate at any time with various media, one of which is the exchange of messages. However, many people do not realize that there are security holes that are used by irresponsible parties to commit crimes such as theft of messages, intercepting messages, and changing the contents of messages. One technique for securing messages is cryptography. Cryptography is the science and art of keeping messages secure when messages are sent from one place to another. Several cryptographic methods that can be used are Advanced Encryption Standard and Caesar Cipher, because the Advanced Encryption Standard method has high security for message security while the Caesar Cipher method has the advantage of being fast in calculations. The combination of these two algorithms in making secret messages is implemented in the form of a mobile-based application to make it easier for users to make secret messages. The results of the encrypted messages formed are difficult to decrypt because they go through 2 stages of the encryption process so that the contents of important messages can be guaranteed confidentiality.